Caribbean - after structural adjustment - Nicholls, Sir Neville (Institute of International Relations St. AugustineTT, 1992)
Emphasises the need to derive new rules for political contests and for the negotiation of stabilization and adjustment programmes with institutions like the multilateral lending agencies. Suggests that adjustment policies must have built into them, measures to cushion their effect on the most vulnerable. Issues a call for increased agricultural production and a change in present economic policies.